Leaching of Chalcopyrite Concentrate in Sulphuric Acid with the Aid of Mechanical Activation and Microwave Energy - Turkmen, Yurdagul; Kaya, Erol (Asian Journal of Chemistry, 2010)
Leaching characteristics of a chalcopyrite concentrate received from Kure Copper Mine, Turkey, were investigated in sulfuric acid solutions. The investigation included the effect of leaching temperature, mechanical activation and microwave energy treatment. The extraction of copper was 10.20 % at conventional conditions in 8 h and it increased to 19.14 % with the mechanical activation. Microwave treatment of the concentrates further increased the extraction of copper to 32.21 % at a leaching temperature of 25 ºC and to 53.74 % at 75 ºC. X-ray analysis revealed the surface chemical alterations of the concentrate samples after microwave irradiation.